2008
DOI: 10.1590/s1415-47572008000100014
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and efficiency of DNA microsatellite markers for paternity testing in horse breeds from the Brazilian Marajó archipelago

Abstract: In this study, 15 microsatellite DNA loci used in comparative tests by the International Society for Animal Genetics were applied to the evaluation of genetic diversity and management, and the efficiency of paternity testing in Marajoara horses and Puruca ponies from the Marajó Archipelago. Based on the genotyping of 93 animals, mean allelic diversity was estimated as 9.14 and 7.00 for the Marajoara and Puruca breeds, respectively. While these values are similar to those recorded in most European breeds, mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
(31 reference statements)
2
13
0
Order By: Relevance
“…In this study, the average number of alleles per locus (6.80, 10 loci out of 18 loci) approximated to the study of white-handed gibbons (Hylobates lar) (7.00 alleles per locus, 8 loci out of 47 loci with fecal samples) (Chambers et al 2004) but was relatively higher than 4.54 alleles per locus (13 loci out of 34 loci with fecal samples) in Yunnan snub-nosed monkeys (Rhinopithecus bieti) (Liu et al 2008). Expected heterozygosity values of 10 microsatellite loci (0.76) were slightly higher than that of 11 loci used in Yugoslav pied cattle (0.75) (Stevanovic et al 2010) and 15 loci used in Marajoara horses (0.75) and Puruca ponies (0.70) (Reis et al 2008). We investigated seven most polymorphic loci and found that our estimate (H o = 0.77, H e = 0.79) showed a slightly higher level of diversity than that of the result (H o = 0.72, H e = 0.72) as reported by Newman et al (2002).…”
Section: Screening Of Microsatellite Loci With Fecal Dnamentioning
confidence: 85%
See 1 more Smart Citation
“…In this study, the average number of alleles per locus (6.80, 10 loci out of 18 loci) approximated to the study of white-handed gibbons (Hylobates lar) (7.00 alleles per locus, 8 loci out of 47 loci with fecal samples) (Chambers et al 2004) but was relatively higher than 4.54 alleles per locus (13 loci out of 34 loci with fecal samples) in Yunnan snub-nosed monkeys (Rhinopithecus bieti) (Liu et al 2008). Expected heterozygosity values of 10 microsatellite loci (0.76) were slightly higher than that of 11 loci used in Yugoslav pied cattle (0.75) (Stevanovic et al 2010) and 15 loci used in Marajoara horses (0.75) and Puruca ponies (0.70) (Reis et al 2008). We investigated seven most polymorphic loci and found that our estimate (H o = 0.77, H e = 0.79) showed a slightly higher level of diversity than that of the result (H o = 0.72, H e = 0.72) as reported by Newman et al (2002).…”
Section: Screening Of Microsatellite Loci With Fecal Dnamentioning
confidence: 85%
“…Among various molecular markers, microsatellites have been demonstrated to be ideal for analyses of genotyping, parentage, and pedigree (Estoup et al 1998, Constable et al 2001, Balloux and Lugon-Moulin 2002, Luna-González et al 2012, Charpentier et al 2012, Yang et al 2014. A growing body of studies has examined the validity of microsatellite in parentage assessment , Reis et al 2008, Luna-González et al 2012, Wojtas et al 2013) and pedigree analysis (Sefc et al 1998, Wang et al 2009, Li et al 2010. Given a sufficient number of alleles, sound results for individual identification and paternity testing could be obtained with relatively small number of microsatellite loci (less than seven) (Bernatchez and Duchesne 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The number of allele (n A ), observed (H o ) and expected heterozygosity (unbiased -H e ) (Nei, 1978), polymorphic information content (PIC) (Botstein et al, 1980), power of discrimination (PD) (Reis et al, 2008;Cerit, 2003), probability of exclusion (PE) (Curi and Lopes, 2002;Cerit, 2003;Řehout et al, 2006), and the paternity index (PI) were calculated for each microsatellite based on the parents' allele frequencies. All of these measures of informativeness were calculated using the Genetix (4.05) (Belkhir et al, 1996(Belkhir et al, -2000, GenAlEx 6 (Peakall and Smouse, 2006), Cervus 3.0 (Marshall, T., 1998(Marshall, T., /2006 and PowerStatsV12 programs (Brenner and Morris, 1990a).…”
Section: Discussionmentioning
confidence: 99%
“…Microsatellite markers have been used extensively for parentage control in different species and are recommended by the International Society for Animal Genetics (ISAG) as they are highly abundant and informative, relatively inexpensive to use, and generate satisfactory results in tests for paternity exclusion (Luikart et al , 1999; Arruga et al , 2001; Curi and Lopes, 2002; Carneiro et al , 2007; Glowatzki-Mullis et al , 2007; Bolormaa et al , 2008; Reis et al , 2008; Carolino et al , 2009; Araújo et al , 2010; Stevanovic et al , 2010; Zhang et al , 2010; Adamov et al , 2011; Saberivand et al , 2011; Visser et al , 2011). …”
Section: Introductionmentioning
confidence: 99%